Film-Forming Chitosan/Poly (vinyl alcohol)–Poly (hexamethylene biguanide) Antiseptic Spray for Wound Cleansing: A Sustainable Healthcare Approach Aligned with Sustainable Development Goals (SDGs) Completed with Bibliometric Analysis - Joel Maria Joju; Tanushree Suresh; Anjana Ajithkumar; Amritha Sajeev; Riju Ramachandran Menon; Anil Kumar Vasudevan; Jayakumar Rangasamy (ASEAN Journal for Science and Engineering in Materials, 2026)
Proper wound cleansing is a fundamental step in preventing infection and supporting effective wound management. This study aimed to develop and evaluate a film-forming antiseptic spray composed of chitosan, polyvinyl alcohol, and polyhexamethylene biguanide for wound cleansing applications. The formulation was prepared using a solution-based approach and characterized in terms of morphology, chemical interactions, sprayability, film formation stability, antibacterial, and antibiofilm performance. The developed spray demonstrated uniform application, stable film formation, and effective incorporation of the antimicrobial agent. Biological evaluations confirmed enhanced antibacterial and antibiofilm activity because of synergistic interactions between the biopolymer matrix and the cationic antiseptic component. This study was further supported by bibliometric evidence indicating a growing global research focus on wound care materials and film-forming antiseptic sprays, emphasizing their relevance to sustainable healthcare innovation. The findings contribute to the advancement of sustainable wound care technologies and align with the Sustainable Development Goals, particularly the goal of promoting good health and well-being.